2D wrinkle assisted zigzag plasmonic chains for isotropic SERS enhancement - Ziwen Yu; Swagato Sarkar; Sezer Seçkin; Ningwei Sun; Anik Kumar Ghosh; Sven Wießner; Ziwei Zhou; Andreas Fery (Scientific Reports)
Abstract Template-assisted colloidal self-assembly has gained significant attention due to its flexibility and versatility. By precisely controlling the shape of the template, it is possible to achieve custom-designed nanoparticle assemblies. However, a major challenge remains in fabricating these templates over large areas at a low cost. Recently, one-dimensional (1D) nano-wrinkle structures have been effectively used for the linear assembly of single-chain or multi-chain nanoparticles, which feature abundant interparticle nanogaps that facilitate efficient plasmonic coupling. To further enhance these assemblies by incorporating diffraction modes, we develop two-dimensional (2D) zigzag wrinkle structures that successfully assemble nanoparticles into plasmonic zigzag chains. Micro spectral measurements and FDTD simulations reveal that zigzag assemblies of plasmonic nanoparticle chains offer isotropic behavior and exhibit stronger plasmonic coupling compared to 1D assemblies, which could be highly beneficial for sensing applications. Due to the responsive PANI shell encapsulating the gold nanoparticles, this 2D zigzag assembly enables flexible tuning of plasmonic resonance under pH regulation.